2014
DOI: 10.1016/j.msea.2014.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing dislocation emission in nanocrystalline materials through shear-coupled migration of grain boundaries

Abstract: a b s t r a c tA theoretical model has been developed to illustrate the effect of shear-coupled migration of grain boundaries on dislocation emission in nanocrystalline materials. The energy characteristics and critical shear stress τ c that is required to initiate the emission process were determined. The results obtained show that the dislocation emission can be considerably enhanced as shear-coupled migration was the dominating process; a critical coupling factor that corresponded to the minimum τ c , which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Investigations of the present authors have shown that the SCM mode can considerably enhance the intrinsic ductility [6], toughness [15], crack blunting [16] and dislocation emission [17] in NC materials. The coupled NGR-SCM process proposed by Li et al [11] has also been identified as an effective toughening mechanism in NC materials [14].…”
Section: Introductionmentioning
confidence: 91%
“…Investigations of the present authors have shown that the SCM mode can considerably enhance the intrinsic ductility [6], toughness [15], crack blunting [16] and dislocation emission [17] in NC materials. The coupled NGR-SCM process proposed by Li et al [11] has also been identified as an effective toughening mechanism in NC materials [14].…”
Section: Introductionmentioning
confidence: 91%
“…The SCM mode has been identified as a general toughening mechanism [20,21], and can considerably enhance the intrinsic ductility of NC materials [22,23]. Moreover, our recent study has shown that SCM was in favor of the dislocation emission from the disclinated grain boundaries [24]. Therefore, one may deduce that SCM could also influence the dislocation emission from a crack tip, thus leading to crack blunting and abundant activation of dislocations in the grain interior, and eventually giving rise to the enhanced ductile feature, which appeared in some NC materials as observed in experiments [3,5,7,8,25].…”
mentioning
confidence: 93%
“…2.6) [85][86][87][88]. Simultaneous GBS and GBM, also called the shear-coupled migration of GBs, result in a grain rotation which changes the GB misorientation angle and can be responsible for the enhancement of dislocation emission in the NC structure [89]. GBS and the shear-coupled migration reduce the energy required for deformation and increase the plasticity of polycrystalline materials [90,91].…”
Section: Grain Boundary Sliding and Grain Boundary Motionmentioning
confidence: 99%